Umbilical Cord : Factors which Influence the Separation Time - Erwin Sarwono; Disse W. S.; Ousdeluys-Murphy H. M; Oosting H.; De Groot C. J. (Indonesian Pediatric Society, 1991)
The separation time of the umbilical cord was studied in 98 healthy Indonesian newborns with the aim of determine the normal time of separation and to evaluate factors which may influence it. The authors looked for a relationship between cord separation and sex, birthweight, gestational age, parity of the mother and nutrition of the newborn. Mean separation time was 10.9 days (SD 3: range 5-23 days). None of the factors analysed had a statistically significant.